Droplet trajectories and collisions in gas forced vortexes: A molecular dynamics study. (2nd February 2022) - Liu, Wenchuan; Li, Ning; Sun, Zhiqian; Wang, Zhenbo; Wang, Zengli
Highlights: Molecular dynamics simulation is performed to study droplets in rotating gas. The droplet trajectories in forced vortexes are observed. A droplet trajectory model based on drag force is proposed. Droplet collisions in forced vortexes are studied. Abstract: Molecular dynamics simulations of droplets in gas forced vortexes by applying a virtual rotational potential were presented. The result showed that the flow field scale of the simulation performed can reflect the macroscopic characteristics. The trajectories of water droplets are longer than that of oil droplets within a certain radius of flow field. A droplet trajectory model was proposed to predict droplet behavior. The study continued to investigate droplet collisions. It was observed that the large oil droplet and the downwind small water droplets produced near head-on, highly off-centre and scraping-adhering collisions, forming stable two-phase interfaces. The slight changes of the interfaces between water and oil droplets under the action of rotating flow field can be reflected by van der Waals interaction. The intermolecular hydrogen bonds form when two water droplets collide. Our study provides a new idea for further understanding of droplet collision in gas flow field.